2019
DOI: 10.1111/ijfs.14188
|View full text |Cite
|
Sign up to set email alerts
|

The influence of exopolysaccharide‐producing lactic acid bacteria on reconstructed ham

Abstract: The influence of in-situ-formed exopolysaccharides (EPS) by lactic acid bacteria (LAB; Lactobacillus sakei TMW 1.411 and Lactobacillus plantarum TMW 1.1478) on the yield and texture of reconstructed ham was investigated. No differences in yield (P > 0.05) were observed but weight loss during storage was significantly higher (P < 0.05) for hams produced with L. sakei 1.411. Furthermore, the produced EPS decreased the hardness (P < 0.05; 50.22 N for control compared to 44.81 N) but did not influence the cohesive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Hilbig et al (2019) found a contrary relationship when using EPS-forming starter cultures in fat-reduced teewurst, in order to cover fat-free parts on protein particles thereby maintaining spreadability (Figure 1). Also in their other studies performed in meat products, HoPSforming strains were found to be more promising (Hilbig et al, 2019a(Hilbig et al, , 2019b(Hilbig et al, , 2020. However, Vincent, Faber, Neeser, Stingele, and Kamerling (2001) indicated in their study that side chains of EPS are of key importance with respect to their texturizing properties although these side chains were shown to convert polysaccharides into more compact structures possessing a lower viscosifying capacity (Cui, 2005).…”
Section: Mechanistic Insights and Structure-function Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hilbig et al (2019) found a contrary relationship when using EPS-forming starter cultures in fat-reduced teewurst, in order to cover fat-free parts on protein particles thereby maintaining spreadability (Figure 1). Also in their other studies performed in meat products, HoPSforming strains were found to be more promising (Hilbig et al, 2019a(Hilbig et al, , 2019b(Hilbig et al, , 2020. However, Vincent, Faber, Neeser, Stingele, and Kamerling (2001) indicated in their study that side chains of EPS are of key importance with respect to their texturizing properties although these side chains were shown to convert polysaccharides into more compact structures possessing a lower viscosifying capacity (Cui, 2005).…”
Section: Mechanistic Insights and Structure-function Relationshipsmentioning
confidence: 99%
“…When it comes to meat matrices, processing conditions and meat matrix composition should be considered with respect to EPS formation and function as illustrated in Figure 1. Since L. sakei TMW 1.411 was found to be a promising strain with regard to structural and textural changes in meat products, it may be a good model in the future to study the impact of processing conditions and meat matrix composition on EPS production in more depth (Hilbig et al, 2019a(Hilbig et al, , 2019b(Hilbig et al, , 2020.…”
Section: Mechanistic Insights and Structure-function Relationshipsmentioning
confidence: 99%
“…Hilbig, Gisder, et al (2019) demonstrated in a recently performed study that the application of in situ JFDS-2019-1246Submitted 8/4/2019, Accepted 11/18/2019 exopolysaccharide (EPS)-producing lactic acid bacteria (LAB) can significantly increase the spreadability of fat-reduced spreadable raw fermented sausages (teewurst). Furthermore, the application of EPS-producing LAB was found to weaken the structure of reconstructed ham (Hilbig, Loeffler, Herrmann, & Weiss, 2019b). Due to these promising results, EPS-producing LAB may also have the potential to maintain the spreadability of onion mettwurst with a lower pH (5.1).…”
Section: Introductionmentioning
confidence: 99%
“…HePS are synthesized out of different substrates in an energy-intensive and complex biosynthesis, which is related to the cell wall biosynthesis (Sutherland, 2001). Since Hilbig et al (2019b) concluded that HoPS-producing LAB showed the best results to maintain the spreadability of fat-reduced spreadable raw fermented sausages, only HoPS-producing LAB were used in the present investigation. HoPS are synthesized by glucosyltransferases out of sucrose and, furthermore, they are composed of only one monomer type D-glucose or L-fructose (2012Rühmkorf, Jungkunz, Wagner, & Vogel, 2012Rühmkorf, Rübsam, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Major microbial food hydrocolloids include fungal polysaccharides such as pullulan from Aureobasidium pullulans and bacterial exopolysaccharides (EPS) such as xanthan from Xanthomonas campestris, gellan from Pseudomonas elodea, and cellulose from Kamagataeibacter xylinus and Acetobacter xylinum. Extensive studies are also continuing to improve viscosity, texture and mouthfeel of dairy and bakery products, and water absorption capacity and textural properties of meat products by using EPS producing lactic acid bacteria in their fermentation (Oluk et al, 2014;Lynch et al, 2018;Hilbig et al, 2019).…”
Section: Hydrocolloids From Microorganismsmentioning
confidence: 99%